Lofty pine and clinging vine: The educational 'Great Gatsby Curve' and the role of house prices - Jing You; Xinxin Ding; Miguel Ni\~no-Zarazúa; Sangui Wang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We investigate the heterogeneous and nonlinear intergenerational transmission channels of education and the impact on this of house price appreciation. Using the China Household Finance Survey 2011, we construct household history of property purchases and educational investment over the past 16 years with current filial educational achievement. Using quantile instrumental regressions, we find that through tightening households' credit constraints, rising house prices weaken the paternal intergenerational educational correlation by 38 per cent (from 0.366 to 0.226) but enhance the maternal correlation by 84 per cent (from 0.165 to 0.303). Decomposition analysis indicates the existence of glass-ceiling effects for females and rural offspring aiming to achieve high educational attainment due to narrower opportunities, and also glass-floor effects for urban offspring due to more endowment, which in turn leads to gender and urban-rural educational gaps across generations. The opportunity effect drives increasing intergenerational persistence of education over time.
Keywords: D31; D63; R31; I24; 330; quantile instrumental regressions; decomposition; housing; intergenerational mobility; education